10% Apis cerana HONEY MOUTH RINSING: ITS EFFECT ON SALIVARY pH OF MECHANICAL ENGINEERING STUDENTS - Haikal Bahresyi; Muslimah; Ani Megawati; Ayuda Nur Sukmawati (Fakultas Kedokteran Gigi Unjani, 2026)
Salivary pH plays an essential role in maintaining oral health. Stable salivary pH levels can be obtained through a mouthwash that buffers salivary pH. Side effects of conventional mouthwash can affect the oral cavity. The most common side effect reported was teeth staining. Honey has several therapeutic properties, including antibacterial and buffering capacities. This study aimed to measure changes in salivary pH before and after gargling with 10% honey solution from Apis cerana bees. This study was conducted on students of mechanical engineering. The participants were divided into three groups: a treatment group, a positive control group (chlorhexidine 0.1%) and a negative control group (distilled water). pH level of each group was measured before and after rinsing. Data were analyzed using the Wilcoxon . Before the pretest, participants brushed their teeth and rinsed with a sugar solution for one minute to acidify and standardize salivary pH. Saliva was then collected using the spitting method. There were no significant differences in the treatment group (p value = 0.881) and the negative control group (p value =0.084). However, there was a significant difference in the positive control group (p-value = 0.002). The pH level of the treatment group showed no significant difference because the average pH of saliva before gargling with honey solution was still within the normal pH range (6.5-7.5). The acidic pH value of honey does not necessarily cause the pH of saliva to become acidic. This happens because the buffering ability of honey helps maintain the stability of saliva pH, so that it can inhibit the growth of acid-producing bacteria. DOI : 10.54052/jhds.v6n1.p53-64